Etiological causes of exudative pleural effusion in patients treated in a teaching hospital (Mediscope, 2017)
The aim of this study was to find out the common etiological causes of exudative pleural effusion in patients before starting treatment. Fifty patients, diagnosed with pleural effusion on admission were randomly selected from Medicine and Paediatric wards of Khulna Medical College Hospital during the period from March 2016 to November 2016. Etiological diagnosis was established by sequential clinical history and findings on physical examination, laboratory tests, chest radiograph, CT scan of the chest and pleural fluid analysis. Patients who remained undiagnosed were subjected to fibro-optic bronchoscopy, thoracoscopic pleural biopsy, and histopathology. Among the patients having pleural effusion, there were tuberculosis, pneumonia, malignancy and systemic lupus erythematosus in 27 (54%), 11 (22%), 7 (14%) and 1 (2%), respectively. Despite all investigations, 4 (8%) were remained undiagnosed etiologically. Most of the pleural effusion cases were diagnosed as tuberculosis. Early and adequate treatment resulted in complete recovery of the patients.Mediscope Vol. 4, No. 1: Jan 2017, Page 30-33